2005
DOI: 10.1038/sj.gt.3302505
|View full text |Cite
|
Sign up to set email alerts
|

Stable transduction of myogenic cells with lentiviral vectors expressing a minidystrophin

Abstract: Gene therapy for Duchenne muscular dystrophy (DMD) will require sustained expression of therapeutic dystrophins in striated muscles. Lentiviral vectors have a relatively large transgene carrying capacity and can integrate into nondividing cells. We therefore explored the use of lentiviral vectors for transferring genes into mouse skeletal muscle cells. These vectors successfully transferred a minidystrophin expression cassette into mdx muscles, and minidystrophin expression persisted and prevented subsequent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 47 publications
0
64
0
Order By: Relevance
“…Our lentivirus construction recapitulates the transduction efficiency of previously tested and published lentivirus vectors [38,39]. We performed FACS analysis to determine the expression of GFP in infected CD133+ normal blood derived cells and we showed a percentage of 60.9% of GFP positive cells demonstrating a good efficiency of transduction as previously described [40,41] (Fig. 3B).…”
Section: Patient Phenotype and Genotype Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our lentivirus construction recapitulates the transduction efficiency of previously tested and published lentivirus vectors [38,39]. We performed FACS analysis to determine the expression of GFP in infected CD133+ normal blood derived cells and we showed a percentage of 60.9% of GFP positive cells demonstrating a good efficiency of transduction as previously described [40,41] (Fig. 3B).…”
Section: Patient Phenotype and Genotype Descriptionmentioning
confidence: 99%
“…The PCR product woas digested with NheI and subcloned into pRRL-cPPT-hPGK-eGFP-WPRE vector. The transduction efficiency of lentiviral vectors containing eGFP and the dysferlin cassette was tested using the same multiplicity of infection as previously described [40,41]. Both lentiviral vectors showed the same transduction efficiency.…”
Section: Lentivector Carrying the Full-length Dysferlinmentioning
confidence: 99%
“…Lentiviral vectors have been used to treat mdx mice locally restoring dystrophin expression at different efficiencies (Kobinger et al, 2003;Li et al, 2005). Kimura and colleagues showed that a lentivirus encoding ÎŒDys intramuscularly injected into 2 weeks old mdx 4cv mice could restore dystrophin in up to 400-1200 fibers in the tibialis anterior muscle.…”
Section: Lentiviral Vectorsmentioning
confidence: 99%
“…However key questions that need to be resolved before this approach could be used in DMD include the optimal vector configuration and the safety profile of the gene delivery methodology. Lentiviral vectors efficiently infect quiescent cells, including stem cells (S. Li et al, 2005) and give long-term, heritable, gene expression because they integrate into the host genome. Drawbacks with lentiviral vectors include possible gene silencing, or mutagenesis (Wilson & Cichutek, 2009), due to the site at which the virus inserts into the host genome.…”
Section: Genetic Modification Of Autologous Cellsmentioning
confidence: 99%
“…A lentiviral vector has been used to insert a 6.8 kb dystrophin mini gene (S. Li et al, 2005), to give rise to a shorter dystrophin protein in regenerated muscle fibers. While these engineered mini-dystrophins appear to retain most of the functional properties of full-length dystrophin, they nevertheless miss important domains, such as the nitric oxide synthase anchoring domain (Lai et al, 2009).…”
Section: Genetic Modification Of Autologous Cellsmentioning
confidence: 99%